Crescimento, hematologia, metabolismo e parâmetros oxidativos de jundiás alimentados com dietas contendo folha de Lippia alba - Marasca, Samuel (2016)
The use of plants as antioxidants is becoming a very important alternative in the food industry and animal production. The Lippia alba is a native plant to Brazil that posses phenolic compounds and essential oils in composition. In this study, the aim was evaluating the inclusion of the leaf from L. alba in the diet from silver catfish (Rhamdia quelen) regarding growth, hematology, metabolism and oxidative parameters. For this, we conducted an experiment lasting 60 days in a re-use water system (20 tanks/250L) with biological filtration. Daily analyzes were performed for the control of chemical and physical parameters of the rearing water. Was used 500 silver catfish (initial weight= 6.22±0.77 g) which were distributed in the experimental units in a completely randomized experimental design (5 treatments and 4 repetitions). L. alba used was grown in UFSM, campus Frederico Westphalen - RS, Brazil. The treatments were: control (no addition leaf); 0.5; 1; 1.5 and 2% inclusion from L. alba leaf powder. All diets had the same composition matrix, containing: 37.49% PB and 10.04% lipídios. The fish were fed to apparent satiety, in three daily meals. At the end of the experiment, they were measured performance parameters and carried out the collection of biological material for evaluation of haematological, metabolic and oxidative parameters. Decrease was observed in growth and smaller in hematological parameters of fish proportional to the inclusion of the leaf in the diets. In higher levels of inclusion of L. alba, occurs undesirable change in metabolis, as increased from alanine aminotransferase in the plasma, indicating liver damage. The presence of L. alba in the diets result in a decreased lipid peroxidation of the muscle and increased of non protein thiols in the gills and muscle. This indicates that the plant has antioxidant potential to silver catfish. Therefore, at the levels tested, the addition of L. alba leaf powder in diets for silver catfish juveniles is not recommended.